2019
DOI: 10.1094/pdis-05-18-0872-re
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic Effects of Thiophanate-Methyl in Multiple Isolates of Sclerotinia homoeocarpa

Abstract: Twenty-eight isolates of Sclerotinia homoeocarpa, causal agent of dollar spot disease in turf, were assessed for fungicide hormesis at sublethal concentrations of thiophanate-methyl (T-methyl). Each isolate was grown in corn meal agar amended with 11 concentrations of T-methyl (30,500 to 0.047 µg/liter), and the area of mycelial growth was determined relative to the control. Three replicates were used per concentration, and the experiment was repeated three to five times for each isolate. Reference isolates (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Fungicide hormesis has profound implications for the application of fungicides. There have been numerous reports on fungicide hormesis, such as stimulatory effects of metalaxyl, mefenoxam, propamocarb, and cyazofamid on plant-pathogenic oomycetes Pythium aphanidermatum and Phytophthora infestans (Garzón et al 2011;Zhang et al 1997), and thiabendazole and thiophanate-methyl on fungal pathogens Penicillium expansum (Baraldi et al 2003) and Sclerotinia homoeocarpa (Pradhan et al 2019). In addition, our laboratory reported hormetic effects of carbendazim (Di et al 2015b), dimethachlone (Zhou et al 2014a), flusilazole (Lu et al 2018a, b), prochloraz (Zhang et al 2019), and trifloxystrobin (Di et al 2016a) on the pathogenicity of S. sclerotiorum.…”
mentioning
confidence: 99%
“…Fungicide hormesis has profound implications for the application of fungicides. There have been numerous reports on fungicide hormesis, such as stimulatory effects of metalaxyl, mefenoxam, propamocarb, and cyazofamid on plant-pathogenic oomycetes Pythium aphanidermatum and Phytophthora infestans (Garzón et al 2011;Zhang et al 1997), and thiabendazole and thiophanate-methyl on fungal pathogens Penicillium expansum (Baraldi et al 2003) and Sclerotinia homoeocarpa (Pradhan et al 2019). In addition, our laboratory reported hormetic effects of carbendazim (Di et al 2015b), dimethachlone (Zhou et al 2014a), flusilazole (Lu et al 2018a, b), prochloraz (Zhang et al 2019), and trifloxystrobin (Di et al 2016a) on the pathogenicity of S. sclerotiorum.…”
mentioning
confidence: 99%
“…This observation indicated that chlorothalonil and thiophanate-methyl might have in vitro hormetic effects on S. cuprophilus . Hormesis to fungicides (e.g., carbendazim, thiophanate-methyl) in some pathogenic fungi, such as Botrytis cinerea and Sclerotinia homoeocarpa , have recently been reported [ 47 , 48 ]. The effects may increase pathogen virulence under periods of sub-lethal fungicide exposure and result in increased disease incidence and severity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In S. sclerotiorum , pretreatment with flusilazole had hormetic effects for later exposure to flusilazole, prochloraz, tebuconazol [ 14 ]. The hormetic effects of pretreatment was also found in Sclerotinia homoeocarpa causing dollar spot disease in turf; when 28 isolates were cultured in corn meal agar containing 11 different concentrations of thiophanate-methyl, the mycelia growth of most preconditioned thiophanate-methyl isolates was significantly enhanced by 3–20% [ 34 ]. In this study, when the stimulated mycelia grown on carbendazim-amended PDA were inoculated on fungicide-free PDA, mycelia growth stimulations were still observed in the second-generation mycelia ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%